Talking About the “Misunderstanding” in the Process of Literary Accepting - Xu Junliu (Lingua Cultura, 2008)
The “misunderstanding” in the process of literary accepting refers to the receiver in the reading text process with the creation main body, creation motive, the work implication, as well as between the works artistic value constitutes the situation which “the dialog” in the complex relations produces contradicts. But, in the concrete reading process, the “misunderstanding” may divide in “the error correction” and “instead harms” kind of situations. Although “the error correction” refers to reader's understanding in line with author's creation original meaning which produces contradicts, but the work itself actually has demonstrated reader’s understood connotation, thus causes this kind of the “misunderstanding” seems cuts with actual and persuasiveness. “Instead harms” refers to the reader unconscious determination to carry on the far-fetched cognition and the appraisal to the literary work, including to literary work non-artistic angle of view twisting. “The error correction” should advocate that “instead harms” should deny, this does not dispute. But, “the error correction” and “instead harms” between has certain fuzzy regions, between them the strict demarcation line, some literary work in such time, possibly has not had “the error correction” in such receiver, but in another time, possibly has the different understanding in other receivers, to “instead harms” direction transformation. The “misunderstanding” is the literature accepts the necessity, because just having the “misunderstanding”, the different sound, between the literature mutual exchanges and collides, the literature only then had prosperously, the vigorous development aspect.